The impact of administrative transaction costs in the EU emissions trading system - Peter Heindl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper empirically investigates the impact of transaction costs for monitoring, reporting, and verification (MRV) of emissions on companies regulated by the EU Emissions Trading System (EU ETS) in Germany. Based on a unique panel dataset, we investigate if MRV costs are dependent on the amount of annual emissions of regulated companies and if there are differences in transaction costs between economic sectors. The results indicate that administrative costs are dependent on the amount of annual emissions for larger companies which has implications for the economic efficiency of the EU ETS. The most important finding, however, is that there are significant differences in MRV transaction costs dependent on the 'type' and 'size' of companies. This implies the existence of considerable economies of scale. Overall, the EU ETS could benefit from reforms by means of a push towards upstream regulation as this would likely increase administrative efficiency.
Keywords: D22; D23; Q58; 330; EU Emissions Trading System; Cap-and-Trade; Transaction Costs; Monitoring; Reporting; and Verification